2017
DOI: 10.1039/c7ra04920j
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on microwave deicing effects on graphite-modified concrete

Abstract: The microwave deicing method is one of the non-contact deicing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…(11) When the surface center temperature T 0 of 0.6CFC3 reaches 0 °C, the temperature rise rate curve shows an increasing trend, but after a short time, there is an inflection point and the temperature rise rate starts to decrease, when the ice thickness decreases and the water layer has basically formed. (12) e temperature rise rate curve for 0.6CFC3 fluctuates in the 100s, compared to 0.6CFC2. It is initially determined that the phenomenon of ice breaking occurs at this time, which in turn triggers the temperature rise rate fluctuation.…”
Section: Effect Of Carbonmentioning
confidence: 93%
See 1 more Smart Citation
“…(11) When the surface center temperature T 0 of 0.6CFC3 reaches 0 °C, the temperature rise rate curve shows an increasing trend, but after a short time, there is an inflection point and the temperature rise rate starts to decrease, when the ice thickness decreases and the water layer has basically formed. (12) e temperature rise rate curve for 0.6CFC3 fluctuates in the 100s, compared to 0.6CFC2. It is initially determined that the phenomenon of ice breaking occurs at this time, which in turn triggers the temperature rise rate fluctuation.…”
Section: Effect Of Carbonmentioning
confidence: 93%
“…e results showed that the surface temperature of the specimen could reach more than 140 °C. In 2017, Liu et al [12] studied the effect of different amounts of graphite on the microwave deicing efficiency of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, estimating the dielectric constant of the concrete wall was challenging because of the dampness caused by recent rainfall. To address this, we calibrated the dielectric constant using known parameters, including the location of the reinforcing bars, and set it as 10.5, which is a reliable value falling within the typical range observed for concrete [13].…”
Section: Gprmentioning
confidence: 99%
“…Wang et al [ 17 ] used steel slag from industrial waste to replace basaltic aggregates to improve the heating properties of asphalt mixtures. Liu et al [ 18 ] modified steel slag particles using the coprecipitation method and evaluated the microwave absorption efficiency as a function of electromagnetic properties and microwave heating rate. Gao et al [ 19 ] also used steel slag instead of aggregates and obtained specimens with an ice-melting efficiency about 2.6 and 2.3 times higher than the ordinary mixture at −5 °C and −20 °C, respectively.…”
Section: Introductionmentioning
confidence: 99%